2022
DOI: 10.1101/2022.08.15.503737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Principles of metabolome conservation in animals

Abstract: Metabolite concentrations shape cellular physiology and disease susceptibility, yet the general principles governing metabolome evolution are largely unknown. Here we introduce a measure of conservation of individual metabolite concentrations among related species. By analysing multispecies metabolome datasets in mammals and fruit flies, we show that conservation varies extensively across metabolites. Three major functional properties, metabolite abundance, essentiality and association with human diseases pred… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…If so, metabolites that are under stronger stabilizing selection in human populations are expected to be more evolutionarily conserved in their concentrations over macroevolutionary time scales. To test this hypothesis, we used a recent approach to infer a score that captures the extent of conservation of metabolite concentrations for individual metabolites based on cross-species comparisons 6 . We focused on a metabolomic dataset containing the relative concentrations of 249 metabolites in four major organs of 26 mammalian species, spanning an evolutionary period of ∼200 million 3 , and calculated an aggregated score of metabolite conservation across the four organs (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If so, metabolites that are under stronger stabilizing selection in human populations are expected to be more evolutionarily conserved in their concentrations over macroevolutionary time scales. To test this hypothesis, we used a recent approach to infer a score that captures the extent of conservation of metabolite concentrations for individual metabolites based on cross-species comparisons 6 . We focused on a metabolomic dataset containing the relative concentrations of 249 metabolites in four major organs of 26 mammalian species, spanning an evolutionary period of ∼200 million 3 , and calculated an aggregated score of metabolite conservation across the four organs (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Second, the agreement between alpha estimate and between-species conservation score suggests that the selective constraints preserving metabolite levels are at least partly shared between human and other mammalian species, including distantly related taxonomic groups. A recent study suggests that variation in evolutionary conservation across metabolites can be explained by a simple model where natural selection preserves flux through key metabolic reactions while permitting the accumulation of selectively neutral changes in enzyme activities 6 . Future works should test the extent to which this general model explains stabilizing selection on human metabolite levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research into the evolution of metabolite levels in mammals found similar results. It has been shown that evolutionary conservation of metabolite levels varies greatly among metabolites and can be explained by a neutral model ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some variations in metabolite levels are likely non-functional (neutral), as evidenced by mutations that strongly impact metabolite levels without measurably altering fitness ( 20 , 21 ). Indeed, it has been recently proposed that much of the between-species variation in tissue metabolite levels in mammals are selectively neutral which are allowed, rather than favored by natural selection ( 22 ). However, the evolutionary driving forces of metabolite levels remain largely unresolved due to a shortage of comparative studies, especially in microbes.…”
mentioning
confidence: 99%